Interactive Animation Media to Increase Children's Reading Interest - Rini Damayanti (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
Indonesian language is the identity of the Indonesian nation. Indonesian lessons become a curriculum in primary education to higher education. The conventional learning system makes it difficult for students to understand the Indonesian language learning materials. In addition, students become less enthusiastic in learning because the learning process is only one way that is from the teacher who explained. Looking at the phenomenon, it takes an innovation in the process of learning Indonesian. The use of interactive educational media in the form of animation can be one way to increase students' reading interest and as a means of introducing information technology. Students can understand how to read the word or sentence Indonesian well and correctly. An attractive display with good visual audio is also one of the students' appeal. On the part of teachers, this interactive educational animation helps facilitate teachers in delivering Indonesian language material that is being discussed. The results to be achieved from making this educational media is improving the ability of students in reading and speak Indonesian well and correctly.